The global role of ppGpp synthesis in morphological differentiation and antibiotic production in Streptomyces coelicolor A3(2) - Hesketh, Andrew (BioMed Central, 2007)
BACKGROUND: Regulation of production of the translational apparatus via the stringent factor ppGpp in response to amino acid starvation is conserved in many bacteria. However, in addition to this core function, it is clear that ppGpp also exhibits genus-specific regulatory effects. In this study we used Affymetrix GeneChips to more fully characterize the regulatory influence of ppGpp synthesis on the biology of Streptomyces coelicolor A3(2), with emphasis on the control of antibiotic biosynthesis and morphological differentiation. RESULTS: Induction of ppGpp synthesis repressed transcription of the major sigma factor hrdB, genes with functions associated with active growth, and six of the thirteen conservons present in the S. coelicolor genome. Genes induced following ppGpp synthesis included the alternative sigma factor SCO4005, many for production of the antibiotics CDA and actinorhodin, the regulatory genes SCO4198 and SCO4336, and two alternative ribosomal proteins. Induction of the CDA and actinorhodin clusters was accompanied by an increase in transcription of the pathway regulators cdaR and actII-ORF4, respectively. Comparison of transcriptome profiles of a relA null strain, M570, incapable of ppGpp synthesis with its parent M600 suggested the occurrence of metabolic stress in the mutant. The failure of M570 to sporulate was associated with a stalling between production of the surfactant peptide SapB, and of the hydrophobins: it overproduced SapB but failed to express the chaplin and rodlin genes. CONCLUSION: In S. coelicolor, ppGpp synthesis influences the expression of several genomic elements that are particularly characteristic of streptomycete biology, notably antibiotic gene clusters, conservons, and morphogenetic proteins.